Pengaruh Good Corporate Governance Terhadap Manajemen Laba Pada Perusahaan Manufaktur Sektor Consumer Non-Cyclicals - Adelya Mutiara Nurhamzah; Sari indah Oktanti Sembiring (Jurnal Pendidikan Ekonomi, 2026)
This study aims to analyze the effect of good corporate governance on earnings management. The population in this study were non-cyclical consumer manufacturing companies listed on the Indonesia Stock Exchange for the 2022-2025 period. The sample selection technique used was purposive sampling, resulting in 53 samples. Data processing was performed using SPSS 25 software. This study employed a quantitative approach with a panel data analysis method. The independent variable in this study was good corporate governance, consisting of managerial ownership, institutional ownership, female board directors, and female audit committee members. While the dependent variable was earnings management, measured using the Discretionary Revenue Model approach by Stubben (2010). The results showed that managerial ownership did not have a positive effect on earnings management, while institutional ownership, female board directors, and female audit committee members did not have a negative effect on earnings management. For future research, it is recommended to use different sectors and extend the research period.